The Effect of Metacognition and Scientific Attitude on the Success in Forming Sakinah Mawaddah Warahmah Families in Career and Non-Career Women - Duski Ibrahim; Sukarno Sukarno (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
This study aims to determine the effect of metacognition and scientific attitudes of family partners in forming a sakinah family. The approach used in this research is descriptive quantitative, which is done by measuring each research variable, then analyzing and describing it so that it is easy to understand. The technique of collecting data is done by survey. Surveys were carried out on all samples in the study to measure metacognition, scientific attitude, and success in forming a sakinah mawaddah warahmah family. The population of this study is women who are grouped into two categories: 1) career women (who work in offices/employees), 2) unemployed women (especially those taking care of the family) in the city of Jambi with a total sample of 100 (50 people in each sample group) taken at random. The instrument used in this study was a set of 30 questions. The answers were measured by respondents using a Likert scale. Dataanalysis was carried out using SPSS 16 software. The results showed thatmetacognition ability significantly affects the ability to form a sakinah mawaddah warahmah family with a sig. 0.012 (career women group) and 0.000 (non-career women group). As for the scientific attitude test, career women obtained 0.031 0.05, and non-career women obtained 0.019  0.05. It shows that scientific attitude significantly affects their ability to form a sakinah mawaddah warahmah family. The F test also shows that the two variables jointly affect the ability to form a sakinah mawadah warahmah family